Resistance of winged bean (psophorcarphus tetragonolobus) to Pseudomonas solanacearum - Abdullah, Hiryati (Malaysian Society of Applied Biology, 1982)
Greenhouse inoculation experiments showed that among the 13 cultivars tested, only UGM loo was found to be immune. All other cultivars showed some resistance, except the susceptible UPS 122. Five of the eleven F₂ generation crosses of winged bean tested showed high resistance. The Germ plasm of winged bean cultivars showed considerable genetic variation to Pseudomonas solanaccarum. Pathogenicity test of P. Solanaccarum to cultivar UPS 122 showed that all isolates from Ginger, french bean and groundnut tested regardless of biotype were non-pathogenic to winged bean. Isolates from Solanaceous host mayor may not be pathogenic depending on isolates. Only isolates From Croton hirtus and Euphorbia prunifolia showed high virulence as the winged bean isolate to Winged bean. Other isolates that were pathogenic to winged bean showed moderate to low virulence Only.